Strategic Leadership in Forming Organizational Culture - Maulidatul Adzimah; Siti Nur Aviatun Hasanah; Hefniy Hefniy (Civiliza Publishing, Indonesia., 2026)
Organizational culture determines whether an educational institution can develop or fall behin. This study aims to analyze the role of strategic leadership in shaping organizational culture in schools. The study used a qualitative approach with a case study. Data sources were obtained from principals, teachers, administrative staff, and students through observation, interviews, and documentation techniques. Data analysis was carried out through the stages of data reduction, data display, and verification or drawing conclusions. The results of the study indicate that strategic leadership plays a very important role in building an organizational culture that is disciplined, communicative, collaborative, and oriented towards improving performance. The principal acts as a director, decision-maker, motivator, and role model in instilling organizational values ​​and forming positive work habits. Organizational culture is developed through routine activities, discipline habits, periodic work evaluations, and open communication that are implemented consistently. Strategic leadership also encourages the organization's ability to adapt to change and increases the effectiveness of achieving school goals. The implications of this study indicate that strengthening the strategic leadership competency of principals needs to be a priority in educational management because it contributes to the creation of a strong, adaptive, and sustainable organizational culture. Thus, the success of an organizational culture is greatly influenced by the leader's ability to align organizational strategy with consistently applied values ​​and work practices.